The Role of Physicians in Approaching Mental Health Issues in Primary Care - Santos, Rafael de Lima; Amorim, Wellington Aparecido Farina de; Santos, Juliana Vallim Jorgetto; Jorgetto, Giovanna Vallim (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Objectives: To analyze the importance of the medical perspective on mental health issues in primary care. Methodology: A scoping review was conducted using the Pubmed, Scielo, and Lilacs databases, with a combination of keywords such as "primary health care," "health professionals," "health promotion," and "mental health." Results: Six articles were included in the review, all 100% produced in Brazil. Regarding the methods employed, qualitative research was present in all articles in this study. The majority (33.3%) of articles were published in the year 2015. Concerning the listed categories, pertaining to studies related to the addressed topic, the peculiarities regarding the medical perspective on mental health issues in primary care were analyzed. Conclusion: The medical perspective on mental health issues in primary care plays a crucial role in improving mental health outcomes for the population. This approach allows for early diagnosis and treatment of mental disorders, the promotion of mental health, and appropriate referrals to specialized services.